Apoptosis-mediated ADAM10 activation removes a mucin barrier promoting T cell efferocytosis - Linnea Z. Drexhage; Shengpan Zhang; Maeva Dupont; Franziska Ragaller; Ellen Sjule; Jose Cabezas-Caballero; Lachlan P. Deimel; Helen Robertson; Rebecca A. Russell; Omer Dushek; Erdinc Sezgin; Niloofar Karaji; et al. (Nature Communications, 2024)
Abstract Efferocytic clearance of apoptotic cells in general, and T cells in particular, is required for tissue and immune homeostasis. Transmembrane mucins are extended glycoproteins highly expressed in the cell glycocalyx that function as a barrier to phagocytosis. Whether and how mucins may be regulated during cell death to facilitate efferocytic corpse clearance is not well understood. Here we show that normal and transformed human T cells express a subset of mucins which are rapidly and selectively removed from the cell surface during apoptosis. This process is mediated by the ADAM10 sheddase, the activity of which is associated with XKR8-catalyzed flipping of phosphatidylserine to the outer leaflet of the plasma membrane. Mucin clearance enhances uptake of apoptotic T cells by macrophages, confirming mucins as an enzymatically-modulatable barrier to efferocytosis. Together these findings demonstrate a glycocalyx regulatory pathway with implications for therapeutic intervention in the clearance of normal and transformed apoptotic T cells.